Application of the Prevention of Disease Concent in Traditional Chinese Medicine in Acupuncture Rehabilitation Treatment of Chronic Diseases： Take Vascular Dementia as an Example - LIU Cunzhi (康复学报)
The concept of rehabilitation prevention is one of the basic theories of rehabilitation medicine of traditional Chinese medicine (TCM), early rehabilitation intervention will help to prevent or reduce the loss of function or disability of patients. This is similar to the theory of preventive treatment of disease in TCM and three-level prevention in modern preventive medicine. Acupuncture and moxibustion has a long history and plays an important role in the preventive treatment of Alzheimer's disease (AD), vascular dementia (VD) and other senile diseases. Taking VD as an example, this paper discussed the rehabilitation treatment of acupuncture and moxibustion of VD and its possible mechanism, which explained that acupuncture and moxibustion therapy played a preventive and therapeutic role in the early stage of dementia, and embodied the TCM concent of "prevent before the disease arises and prevent disease from exacerbating". The early intervention of TCM rehabilitation technology can transform forward the focus of prevention and control of chronic diseases. To construct a new model of intelligent rehabilitation of TCM based on the theory of preventive treatment of disease, and develop a standardized acupuncture and moxibustion rehabilitation technology with the assistance of internet and information construction, which will help to improve the effectiveness, safety and patient compliance of TCM acupuncture and moxibustion rehabilitation services, and will contribute to advancing the healthy China.